TỔNG HỢP VÀ NGHIÊN CỨU CÁC PHỨC CHẤT CỦA MỘT SỐ NGUYÊN TỐ ĐẤT HIẾM (Pr, Nd, Eu, Gd) VỚI DL-ALANIN - Thanh Lê, Đặng Thị; Thiềng, Lê Hữu; Đức, Lý Minh (Vietnam Journal of Science and Technology, 2012)
SUMMARY SYNTHESIS AND STUDY ON THE COMPLEXES OF SOME RARE EARTHS (Pr, Nd, Eu, Gd) WITH DL-ALANINE The complexes of some rare earths with DL-alanine were synthesized. These solid complexes have the general formula [Ln(Ala)3]Cl3.3H2O [Ln: Pr, Nd, Eu, Gd and Ala: CH3CH(NH2)COOH]. The structure of the complexes have been recognised on the basic of elemental analysis, conductivity measurements, IR spectra and thermal analysis methods. It was found that the DL-alanine utilized amino nitrogen and carboxyl oxygen for bonding. Keyword. Rare earth complex, alanine, synthesis, thermal analysis